(3TQM GdefgGLs - (3CHh GdYHGS CMeO Hf MeOGf Hf CMeO GdCPQYis; (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3Ydi Hf eMeO Hf CHj HcQ Hf eMeO GdSYi s)
(3ChdgG (B:s
(3jHOC HHGH RcGI GdfbO s
(3BNQgG (B:s
(3BNQg HGH GdEMUGQ hGdahGJ ef cJGH GdML s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eLdOI efgbhHdJ SfI (B843 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs